Ambulatory Care Pharmacist Perception of Formulary Medication Shortage: Tertiary Center Experience. (August 2022) - Jaser, Saud; Al Aamer, Kholoud; Al Anizi, Abdulaziz; Javed, Nargis Begum; AL-Mohaithef, Mohammed
Background: Medication shortage is a serious issue affecting public health and patient care. It causes a major burden on the medical team of a healthcare organization in the delivery of quality care.Objectives: This study aims to assess the perception of ambulatory care pharmacist about formulary medication shortage as well as to assess the rate of medication shortage and explore the highest classes of the not-available (NA) medication.Methods: A cross-sectional survey was performed to assess pharmacist perception regarding medication shortage. The data for NA medication was collected from the hospital health information system "HIS" (Best care) to investigate the type and classes of medication shortage.Results: The overall survey response rate was 92.7%. The majority (61%) of participants encountered 5 to 15 labels of NA medication per day, 43% of participants encountered unpleasant behavior from patients usually due to NA medication and the main reason of patient dissatisfaction was the negative effect of NA medication on their course of therapy. Ninety-seven percent of participants agreed that medication shortage adds extra pressure/workload and 66% agreed that medication shortage increases the chance of medication error. A total of 113 medication shortage was recorded between January and March 2020. The 2 drug classes, which showed maximum shortage, were gastrointestinal and cardiovascular medications. The most prevalent type of medication shortage was for drugs administered by oral route (91.2%).Conclusions: The study provides insights into the frequency, management, and problems confronted due to medication shortage from the pharmacist perception. The study findings highlight the classes and type of medication shortage in the hospital which needs intervention to enhance patient care. The findings of the study would help the higher administration to implement an effective strategy to mitigate the shortage of medication, improve patient satisfaction, and to reduce pharmacist workload.